Human Factors of Cybersecurity - AL-BADAYNEH , DIAB M.; AL-BADAYNEH, DARA D.; HASHISH, RABAB K. (Journal of Posthumanism, 2025)
Human factors significantly impact cybersecurity, improving security efficiency or creating vulnerabilities for hackers. Employee behavior, decision-making, and communication can lead to security breaches. Human factors play a crucial role in cybersecurity, often overlooked compared to physical and technological safeguards. These factors are usually static, leading to a lack of assurance in their role in the cybersecurity chain. Recognizing and valuing the human element is essential for achieving or deteriorating security principles, addressing various types of cyberattacks, addressing challenges associated with human factors, safeguarding organizations from data breaches, maintaining reputation, and protecting financial security.The absence of interdisciplinary cooperation in the technology industry means products do not consider users' cognitive and emotional demands, especially in cybersecurity, where human factors and engineering concepts are primarily relied upon. This lack of criminological, sociological, and psychological expertise exacerbates human vulnerabilities, leading to products that fail to account for users' social, cognitive, and emotional needs, highlighting the need for a more comprehensive approach to human behavior. Research highlights the fallacy in relying on technological solutions to address human vulnerabilities in cybersecurity, highlighting the need for a more holistic approach that considers human behavior and performance.